Effect of Pitch to Height Ratio on Flow Visualization, Heat Transfer, and Thermal Performance in a Round Tube with Upstream RWVG - Withada Jedsadaratanachai; Nuthvipa Jayranaiwachira (My University, 2014)
Fully developed periodic laminar flow and heat transfer in an isothermal wall tube with 45° upstream rectangular winglet vortex generators (RWVG) with closed end are investigated numerically. The fluid flow and heat transfer characteristics are proposed for Reynolds numbers based on the diameter of the tube, Re = 100 to 2000. The RWVGs with an attack angle of 45° are mounted with in-line arrangement on both sides of a plate and the closed tip pointing upstream is inserted in the middle of the tested tube to produce longitudinal vortex flows through the tested section. Effects of different blockage ratios (b/D, BR) and pitch spacing ratios (P/D, PR) on heat transfer, pressure loss, and the thermal enhancement factor (TEF) in the round tube are studied. The results show that the longitudinal vortex flows can induce impinging flows on a tube wall leading to an extreme increase in heat transfer rate over the round tube for all cases. Additionally, the rise in the BR and the reduction of PR result in the increase of both the Nusselt number and friction factor values. The optimum TEF in the range studied is around 2.9 at BR = 0.15, PR = 1, and Re = 2000.
Keywords: Heat transfer enhancement; Wingtip device; Vortex generator; Heat Transfer Mechanisms